2016
DOI: 10.5194/acp-2016-639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anthropogenic influences on the physical state of submicron particulate matter over a tropical forest

Abstract: <p><strong>Abstract.</strong> The occurrence of non-liquid and liquid physical states of submicron atmospheric particulate matter (PM) downwind of an urban region in central Amazonia was investigated. Measurements were conducted during two Intensive Operating Periods (IOP1 and IOP2) that took place during the wet and dry seasons, respectively, of the GoAmazon2014/5 campaign. Air masses representing variable influences of background conditions, urban pollution, and regi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
0
23
1
Order By: Relevance
“…For example, pollution may mask some of the influences of forest loss on Amazonian rainfall (Cox et al 2008). Interactions can also be complex, for example, the isoprene derived particles found over the Amazon typically adhere to each other allowing aggregation and increased size but smoke reduces this aggregation (Bateman et al 2017). As another example, while forest loss generally reduces BVOC emissions, some land uses are major sources.…”
Section: Anthropogenic Impactsmentioning
confidence: 99%
“…For example, pollution may mask some of the influences of forest loss on Amazonian rainfall (Cox et al 2008). Interactions can also be complex, for example, the isoprene derived particles found over the Amazon typically adhere to each other allowing aggregation and increased size but smoke reduces this aggregation (Bateman et al 2017). As another example, while forest loss generally reduces BVOC emissions, some land uses are major sources.…”
Section: Anthropogenic Impactsmentioning
confidence: 99%
“…The IM_OC scheme was designed as a sensitivity test to consider observations that showed that OC from anthropogenic sources can be nonliquid even at high relative humidity (RH) and exist in an EM state in the Amazon ( 33 ). Thus, these particles would not participate in thermodynamic processes that allow semivolatile gases to partition to the particle phase.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the sensitivity study for the distribution of SOA associated with OC (based on the finding from ref. 33 ) is simplified. As new knowledge is developed, our simplified treatment will need to be expanded, based on knowledge of the physical and chemical characteristics of aerosols and their mixing with SOA.…”
Section: Implications and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the region is a valuable laboratory for studying the impact of anthropogenic emissions of air pollutants. Although, there are a number of studies involving the measurements of atmospheric pollutants in the Amazon region (e.g., Kuhn et al, 2010;Trebs et al, 2012;Baars et al, 2012;Artaxo et al, 2013), most of the contribution was published very recently with the results of the GoAmazon project (Martin et al, 2016a;Martin et al, 2016b;Alves et al, 2016;Pöhlker et al, 2016;Sá et al, 2016;Kourtchev et al, 2016;Hu et 55 al., 2016;Bateman et al, 2016;Cecchini et al, 2016;Jardine et al, 2016). In terms of numerical studies, only a few studies focusing the role of the anthropogenic emission sources in urban area are available (Freitas et al, 2006;Andreae et al, 2012;Beck et al, 2013;Bela et al, 2014).…”
Section: Introductionmentioning
confidence: 99%